STRATEGI PENGEMBANGAN AGROINDUSTRI KERIPIK SINGKONG DI KECAMATAN MAPANGET KOTA MANADO - Sulaiman ., Yasin; Tommy F. Lolowang; Welson ., Wangke; Theodora M. Katiandagho (Sam Ratulangi University, 2016)
This research purpose to identify about internal and external factor at keripik singkong agro-industry in Mapanget District, Manado City by formulating some strategies including SWOT matrix. The factor that become the main strength is production periodically, while the weakness factors is in transportation infrastructure. The Factors which became opportunity is creating jobs. The threat is in the nature erratic weather, there is support from the government, but lack of response from employers, agro-industry and human resources that have not been trained. Based on the result of research, it can be concluded that the appropriate strategy for agro-industry development of keripik singkong in Mapanget District Manado City is to apply aggressive strategy, that is improving the quality of technologies, from simple technology to modern renewable technologies: increase capital to improve business productivity and productivity of agro-industrial raw materials of farmers; add flavor product innovation Keripik Singkong to be varied so it could be increase consumer interest; in cooperation not only with suppliers (farmers) to ensure the availability of raw materials; employers should be more enthusiastic about the development of products related to the legality of its business; improving the quality of raw materials into organic raw materials; increase production to get benefit sustainbly and Coorporate with financial institutions such as banks to raise capital; collaborate with farmers who have the quality and quantity of good raw materials and take advantage of government support for training the workforce, for additional capital, and certification of products.*ls